Mathematical modelling of patient flows to predict critical care capacity required following the merger of two district general hospitals into one. (29th September 2014) - Williams, J.; Dumont, S.; Parry‐Jones, J.; Komenda, I.; Griffiths, J.; Knight, V.
Summary There is both medical and political drive to centralise secondary services in larger hospitals throughout the National Health Service. High‐volume services in some areas of care have been shown to achieve better outcomes and efficiencies arising from economies of scale. We sought to produce a mathematical model using the historical critical care demand in two District General Hospitals to determine objectively the requisite critical care capacity in a newly built hospital. We also sought to determine how well the new single unit would be able to meet changes in demand. The intention is that the model should be generic and transferable for those looking to merge and rationalise services on to one site. One of the advantages of mathematical modelling is the ability to interrogate the model to investigate any number of different scenarios; some of these are presented.